2019
DOI: 10.1155/2019/9043675
|View full text |Cite
|
Sign up to set email alerts
|

Live Cell Imaging Supports a Key Role for Histone Deacetylase as a Molecular Target during Glioblastoma Malignancy Downgrade through Tumor Competence Modulation

Abstract: Glioblastoma (GBM) is the most aggressive tumor of the central nervous system, and the identification of the mechanisms underlying the biological basis of GBM aggressiveness is essential to develop new therapies. Due to the low prognosis of GBM treatment, different clinical studies are in course to test the use of histone deacetylase inhibitors (iHDACs) in anticancer cocktails. Here, we seek to investigate the impact of HDAC activity on GBM cell behavior and plasticity by live cell imaging. We pharmacologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…While it is known that HDAC1 and HDAC2 (class I HDACs) harbor highly specific and nonoverlapping roles in the developing brain, it is unclear whether these nonredundant functions are retained in glioma cells (2,13). Our current knowledge on the role of HDACs in GBM is primarily based on pan-HDACi studies and isoform-specific knockdown or knockout experiments in serum-grown, long-term cultures of GBM cells and not in GSCs (14)(15)(16)(17)(18)(19)(20). Even the Cancer Dependency Map project, which profiled hundreds of cancer cell lines to identify genetic and pharmacological vulnerabilities, utilized traditionally grown glioma cell lines (20).…”
Section: Introductionmentioning
confidence: 99%
“…While it is known that HDAC1 and HDAC2 (class I HDACs) harbor highly specific and nonoverlapping roles in the developing brain, it is unclear whether these nonredundant functions are retained in glioma cells (2,13). Our current knowledge on the role of HDACs in GBM is primarily based on pan-HDACi studies and isoform-specific knockdown or knockout experiments in serum-grown, long-term cultures of GBM cells and not in GSCs (14)(15)(16)(17)(18)(19)(20). Even the Cancer Dependency Map project, which profiled hundreds of cancer cell lines to identify genetic and pharmacological vulnerabilities, utilized traditionally grown glioma cell lines (20).…”
Section: Introductionmentioning
confidence: 99%
“…TNTs were first identified by Rustom et al in pheochromocytoma PC12 cells [95]. Since then, a variety of in vitro studies have reported the presence of TNTs in several cell types, including GBM [99][100][101][102]. Moreover, reports have shown that communication between GBM and other central nervous system cells such as astrocytes [102,103] and microglia [100] can occur through TNTs.…”
Section: Other Alternative Cytoskeletal Therapeutic Targets Against G...mentioning
confidence: 99%
“…GBM-specific investigations have shown valproic acid treatment in vitro causes increased p21 WAF1/Cip1 expression in multiple cell lines and sensitization to TMZ treatment in GBM cell lines but not in primary GSC cultures derived from human tumors ( 70 , 71 ). Vorinostat (suberoylanilide hydroxamic acid, SAHA), a selective inhibitor of HDACs 1, 2, 3, and 6, has been used to treat certain types of cutaneous T cell lymphoma and has demonstrated similar ability to radiosensitize patient-derived GBM cell cultures in vitro , with this effect acting synergistically with a Bcl-2 pathway inhibitor, obatoclax ( 72 75 ). U87 cells treated with vorinostat exhibited cell cycle arrest in G 0 /G 1 and reduced cell motility, whereas other studies have reported conflicting results for these phenotypes in patient-derived GBM cell lines ( 75 , 76 ).…”
Section: Histone Acetylationmentioning
confidence: 99%
“…Vorinostat (suberoylanilide hydroxamic acid, SAHA), a selective inhibitor of HDACs 1, 2, 3, and 6, has been used to treat certain types of cutaneous T cell lymphoma and has demonstrated similar ability to radiosensitize patient-derived GBM cell cultures in vitro, with this effect acting synergistically with a Bcl-2 pathway inhibitor, obatoclax (72)(73)(74)(75). U87 cells treated with vorinostat exhibited cell cycle arrest in G 0 /G 1 and reduced cell motility, whereas other studies have reported conflicting results for these phenotypes in patient-derived GBM cell lines (75,76). In addition to these phenotypic changes, treatment with vorinostat was found to significantly alter the transcriptomic landscape of patient-derived GBM cell lines, with gene expression profiling revealing a shift away from TCGA proneural and classical molecular signatures towards a neural signature, though the existence of this particular molecular subtype has been questioned in more recent work (76,82,83).…”
Section: Panobinostatmentioning
confidence: 99%